2020
DOI: 10.1016/j.healun.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of chronic lung allograft dysfunction phenotypes: Validation and proposed refinement of the 2019 International Society for Heart and Lung Transplantation classification system

Abstract: BACKGROUND: Chronic lung allograft dysfunction (CLAD) is a heterogeneous condition. Characterization of CLAD phenotypes is essential to enhance the understanding of pathogenesis and guide new therapies. The study objective was to validate the new International Society for Heart and Lung Transplantation (ISHLT) CLAD classification system and further explore patients who do not fall into the defined CLAD sub-categories. METHODS: We performed a single-center, retrospective cohort study of adult, first, bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 20 publications
5
72
0
Order By: Relevance
“…Patients were excluded from CLAD analysis if they had < 4 PFT measurements post‐transplant, <90 days survival, or if they developed CLAD prior to detection of eosinophils in TBBx. CLAD phenotype was defined by the 2019 Consensus criteria [2,22,23].…”
Section: Methodsmentioning
confidence: 99%
“…Patients were excluded from CLAD analysis if they had < 4 PFT measurements post‐transplant, <90 days survival, or if they developed CLAD prior to detection of eosinophils in TBBx. CLAD phenotype was defined by the 2019 Consensus criteria [2,22,23].…”
Section: Methodsmentioning
confidence: 99%
“…In one cohort, the median survival after RAS diagnosis was 541 days, compared to 1421 days in the BOS group 6 . Other studies have found even less favorable outcomes, with the time to death or re‐transplantation being 372 days in RAS and 500 days in BOS 32 . Today, the average survival after the diagnosis of RAS is estimated to be between 6 and 18 months, compared to 3–5 years after BOS 9 …”
Section: Outcome/mortalitymentioning
confidence: 97%
“…Finally, pediatric lung transplants occur less frequently compared to adults, making not only detection and recognition of complications, but also coordinating randomized control trials to investigate them difficult. 24,26,32 Most therapeutic and treatment strategies for RAS in the pediatric population are extrapolated from adult and animal literature.…”
Section: Pe D I Atr I C Datamentioning
confidence: 99%
See 2 more Smart Citations